THE EFFECT OF MATRICULATION AND FAMILIARIZATION WITH NEW STUDENTS TO SUPPORT UNDERSTANDING LESSONS IN INDONESIAN NAVAL TECHNOLOGY COLLEGE - Mukhlis Mukhlis; Rahkmad Susilo; Anton Nugroho (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
Matriculation is the lecturing before the real formal study in STTAL that has resulted in all students adapting to all lessons because the students who study in STTAL have various backgrounds. Especially for post-graduates and diplomas . They have different background education, therefore they have to get warmed up in the lessons for two months. The familiarization has resulted in the students adapting to living in STTAL because they have to live in a dormitory . The familiarization can help them orientation about activities and all rules in college. The result of this research is to find out the correlation between matriculation, familiarization and understanding of the lessons during the study in STTAL. This research uses a descriptive and quantitative approach using tools SPSS to aim a data analyzer. The responders are students with postgraduate, undergraduate, and diplomas who study in STTAL total 130 students and who have done matriculation and familiarization when they are new students and give good feedback in the questionnaire. In this research, the result tcount value X1 is 21,778 > ttable 1,980 and the tcount X2 value is 11,627 > ttable (1,980) so H0 was accepted so there are relations between matriculation and familiarization to understanding lessons in STTAL. The college has to develop equipment for matriculation and familiarization so students can adapt vastly. Keywords: Matriculation, Dormitory, SPSS